Professional Golf—A License to Spend Money? Issues of Money in the Lives of Touring Professional Golfers. (June 2015) - Fry, John; Bloyce, Daniel; Pritchard, Ian
Drawing on figurational sociology, this article examines issues of money that are central to touring professional golfers' workplace experiences. Based on interviews with 16 professionals, results indicate the monetary rewards available for top golfers continues to increase; however, such recompense is available to relatively small numbers and the majority fare poorly. Results suggest that playing on tour with other like-minded golfers fosters internalized constraints relating to behavior, referred to as "habitus, " whereby many players "gamble" on pursuing golf as their main source of income despite the odds against them. Golfers are constrained to develop networks with sponsors for financial reasons, which has left some players with conflicting choices between regular money, and adhering to restrictive contractual agreements, or the freedom to choose between different brands.